Comparison of the risk of acquiring in vitro resistance to doripenem and tazobactam/piperacillin by CTX-M-15-producing Escherichia coli. Issue 5 (May 2015) - Horiyama, Tsukasa; Kanazawa, Sachi; Hara, Takafumi; Izawa, Masaaki; Sato, Takafumi; Yamaguchi, Takahiro; Tsuji, Masakatsu; Maki, Hideki
Abstract: To compare the risk of acquiring in vitro resistance between doripenem and tazobactam/piperacillin by CTX-M-15-producing Escherichia coli, the in vitro frequency of resistance was determined. Four strains carrying multiple β-lactamases such as bla OXA-1 or bla CTX-M-27 as well as bla CTX-M-15 and bla TEM-1 were used. No resistant colonies appeared on doripenem-containing plates, whereas resistant colonies were obtained from three of four test strains against tazobactam/piperacillin using agar plate containing 8- to 16-fold MIC of each drug. These three acquired tazobactam/piperacillin-resistant strains were not cross-resistant to doripenem, and they showed 1.9- to 3.1-fold higher piperacillin-hydrolysis activity compared to those of each parent strain. The change of each β-lactamase mRNA expression measured by real-time PCR varied among three resistant strains. One of three tazobactam/piperacillin-resistant strains with less susceptibility to ceftazidime overexpressed both bla CTX-M-15 and bla TEM-1, and the other two strains showed higher mRNA expression of either bla TEM-1 or bla OXA-1 . These results demonstrate that multiple β-lactamases carried by CTX-M-15-producing E. coli contributed to the resistance to tazobactam/piperacillin. On the other hand, these resistant strains maintained susceptibility to doripenem. The risk of acquiring in vitro resistance to doripenem by CTX-M-15-producing E. coli seems to be lower than that to tazobactam/piperacillin.